2016
DOI: 10.1111/famp.12235
|View full text |Cite
|
Sign up to set email alerts
|

Family Interventions for Schizophrenia and the Psychoses: A Review

Abstract: Family psychoeducation as a treatment for schizophrenia was developed 40 years ago almost simultaneously and independently by investigators who at the time were not family therapists. Although the original goal was to decrease high expressed emotion as a means of preventing relapse, later variations have gone beyond to focus on social and role functioning and family well-being. Explicitly disavowing the earlier assumptions that family pathology caused relapse and deterioration, family psychoeducation seeks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 126 publications
(180 reference statements)
4
178
0
14
Order By: Relevance
“…Considering these findings, authors recommended that family interventions should be offered to families of those with schizophrenia. Several studies and subsequent reviews reported similar results (55,83,92,94,95). Support for family intervention also resulted in some national guideline recommendation that treatment would be offered to caregivers (49,73).…”
Section: Family Interventionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Considering these findings, authors recommended that family interventions should be offered to families of those with schizophrenia. Several studies and subsequent reviews reported similar results (55,83,92,94,95). Support for family intervention also resulted in some national guideline recommendation that treatment would be offered to caregivers (49,73).…”
Section: Family Interventionsmentioning
confidence: 72%
“…There are several variations of family interventions, but most commonly family psychoeducation consists of strategies to effectively work with a relative with schizophrenia, and to increase collaboration between family members and clinical care providers. Family psychoeducation typically reviews content about illness, medication and treatment management, coordination of services, problem solving, coping and rehabilitative services, and crisis planning, as well as discussion about expectations and distress, as well as social support (92).…”
Section: Family Interventionsmentioning
confidence: 99%
“…E se ao doente é dado apoio e orientação antes e depois da alta o mesmo não acontece às famílias. A inexistência de programas estruturados com vista a preparar uma alta responsável e segura, cria dinâmicas de grande stresse no seio da família, sendo o grupo de suporte um recurso utilíssimo, mas de efeito escasso para a amplitude do problema de cuidar de uma pessoa com DMG em casa (Mcfarlane, 2016). Assim, importa mudar as conceções de cuidados à família ainda existentes, mais centrados na satisfação das necessidades do cliente e se avance para uma conceção de cuidados centrada no doente e família e no seu potencial de desenvolvimento.…”
Section: Discussionunclassified
“…A evidência em outras realidades semelhantes sugere a efetividade deste tipo de intervenção para os familiares das pessoas doentes (Grácio, Gonçalves-Pereira, & Leff, 2015;McFarlane, 2016 (Strauss e Corbin, 1998).…”
Section: Introductionunclassified
“…Family interventions, including psychoeducation for schizophrenia, have proved to be one of the most consistently effective treatment modalities available, with relapse rate reduction at 50-60% over treatment as usual [1,2]. Besides relapse severity reduction, psychoeducation leads to less frequent relapses, better treatment adherence, lower self-stigma, better quality of life, improvement of social competencies, active engagement in rehabilitation, and lower cost of care, either alone or as a part of complex treatment regimen [3][4][5][6][7].…”
Section: What Is Psychoeducation and Where Does It Help?mentioning
confidence: 99%